How to survive a robot invasion : rights, responsibility, and AI - Gunkel, David J. (Routledge, 2020)
In this short introduction, David J. Gunkel examines the shifting world of artificial intelligence, mapping it onto everyday twenty-first century life and probing the consequences of this ever-growing industry and movement. The book investigates the significance and consequences of the robot invasion in an effort to map the increasingly complicated social terrain of the twenty-first century. Whether we recognize it as such or not, we are in the midst of a robot invasion. What matters most in the face of this machine incursion is not resistance, but how we decide to make sense of and respond to the social opportunities and challenges that autonomous machines make available. How to Survive a Robot Invasion is a fascinating and accessible volume for students and researchers of new media, philosophy of technology, and their many related fields. It aims both to assist readers' efforts to understand a changing world and to provide readers with the critical insight necessary for grappling with our science fiction-like future.